Shoot organogenesis and plant regeneration of Achyranthes japonica - Yoo, Ji Hyun (Journal of Phytology, 2024)
This study focused on the in vitro plant regeneration and micropropagation of Achyranthes japonica Nakai by employing various cytokinins and auxins to determine their effects on shoot and root elongation. Seed sterilization was conducted utilizing a 70% solution of ethanol and subsequent sodium hypochlorite treatment. Seeds were germinated on Murashige and Skoog medium. Shoot regeneration was assessed by placing stem nodes, which were excised from the in vitro plants, on the supplemented medium. The effects of various cytokinin concentrations, BAP, kinetin, TDZ, and zeatin were analyzed. According to the results, TDZ at 2.0 mg/L demonstrated the highest number of effects of regeneration of shoots with minimal growth of 3.6±0.4 mm. At the same time, supplementation of kinetin without auxins leads to longer shoot length (17.2±2.1 mm). The addition of auxins such as IAA and IBA along with kinetin showed that the shoot length was increased than that of the control. The effects of AgNO3 and putrescine on shoot regeneration were also analyzed. It was stated that AgNO3 at 10 mg/L provided the most suitable shoot induction (3.8±0.49 shoots/explant). In addition, it is shown that among the various auxin concentrations, 0.1 mg/L IBA is the most suitable concentration for root regeneration (11.4±2.5 roots/shoot). The results imply that hormonal concentrations have significant effects on plant regeneration. Overall, these results identify the potential need for further research concerning the micro propagational techniques of A. japinca and similar plants.